(untitled) (Diametros, 2005)
The article reconstructs, develops, and analyzes the arguments used by opponents of the legalization of marriages between homosexuals. In particular, two types of arguments used in public debates are criticized, the argument based on moral convictions and the argument based on such sociological facts as the decline of fertility or the crisis of the family. An analysis of the first argument leads to the conclusion that moral convictions cannot be used to justify opposition towards concrete legal regulations, if the latter are addressed to persons who hold differ opinions on moral issues. The sociological argument, in turn, is based on unjustified prognoses of the legalization of same-sex marriages. The article concludes that in their present form both of the above arguments are incorrect.